1995
DOI: 10.1530/eje.0.1320306
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone-binding protein-related immunoreactivity in the serum of patients with acromegaly is regulated inversely by growth hormone concentration

Abstract: In this report we describe a newly developed radioimmunoassay (RIA) for the determination of the high-affinity growth hormone-binding protein (GHBP) in human blood. Using this RIA for the measurement of GHBP in serum of 29 patients with acromegaly, decreased concentrations were found compared to the normal range, depending on the activity of the disease. Growth hormone-binding protein was correlated inversely to log GH (r = -0.7, p < 0.001). A weaker relationship was shown between the GHBP activity determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 19 publications
(24 reference statements)
2
22
2
Order By: Relevance
“…Uric acid was determined with the uricase method (Kodak, Rochester, NY, USA), insulin by a radioimmunoassay (International CIS, Gifsur-Yvette, France) and IGF-I by an ELISA after acid ethanol extraction as described previously. 23 Leptin 24 and GHBP 25 were measured by recently described speci®c in-house' RIAs. Intra-and interassay coef®cients of variation in all immuno-assays were below 9% at half maximum displacement tracer.…”
Section: Methodsmentioning
confidence: 99%
“…Uric acid was determined with the uricase method (Kodak, Rochester, NY, USA), insulin by a radioimmunoassay (International CIS, Gifsur-Yvette, France) and IGF-I by an ELISA after acid ethanol extraction as described previously. 23 Leptin 24 and GHBP 25 were measured by recently described speci®c in-house' RIAs. Intra-and interassay coef®cients of variation in all immuno-assays were below 9% at half maximum displacement tracer.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have, however, suggested that the circulating binding protein is also cleaved from a truncated receptor lacking 97.5% of the intracellular part, which is a result of an alternatively spliced mRNA (27,28). High levels of GHBP have been found in conditions with low GH levels, including simple obesity (7,29) and vice versa in, for example, acromegaly and insulin-dependent diabetes mellitus (7,(30)(31)(32)(33). These data suggest that the GH receptor in some way is up-regulated in GH-insufficient conditions.…”
Section: Figurementioning
confidence: 99%
“…As GH-binding protein (GHBP) is believed to be derived from proteolytic cleavage of the extracellular domain of the GH receptor and may be regarded as an intrinsic part of the GH-IGF-I axis, an effect of body composition on circulating GHBP levels may be expected (10,11). Some studies have shown that GH and insulin might participate in regulation of GHBP levels (12,13). Little is known, however, about GH secretion and GHBP variations in obesity according to the degree of glucose tolerance.…”
Section: Introductionmentioning
confidence: 99%